The Chilling Effects of Obstacles to Accessing, Using, and Sharing In-Copyright Data for Quantitative Research. - Aufderheide, Patricia; Butler, Brandon; Anastacio, Kimberly (Information & Culture, 2024)
The article explores the challenges researchers face when conducting text and data mining (TDM) due to copyright restrictions. It highlights issues such as limited access to data, confusing license terms, and restrictions on data use and sharing. These obstacles can lead to changes in research design, limited scope and quality of research, and delays in obtaining data. The article suggests solutions such as deidentifying and sharing datasets, collaborating with data owners, and implementing policies that support TDM research. It emphasizes the need for governments to address restrictive copyright laws and expand open access to government databases to facilitate TDM research.